A clinical study of management of wounds using vacuum assisted dressings - Patra, Sanat Kumar; Mohapatra, Minati; Panda, Srikant; Sarangi, Ashok Kumar; Babu, K. Kiran; Sarangi, Anshuman (International Journal of Advances in Medicine, 2022)
Background: The application of controlled levels of negative pressure has been shown to accelerate debridement and promote healing in many different types of wounds. Vacuum assisted closure (VAC) has proved its efficacy for wound dressing leading to faster wound healing and shorter hospital stay. The aim of the study was to determine the advantage of vacuum assisted closure over conventional dressing in SCBMCH hospital. Methods: The study was conducted at general surgery wards of SCB Medical College hospital. After debridement of the wound vacuum assisted dressing was applied. Control group was given conventional dressing. Results: In the study sample 10% patients were less than 40 years, 76% belonged to 41-60 age group and 7% were more than 61 years of age, 60% male and 40% female. Wounds were located in the foot 27 (54%), leg 19 (38%), sole 2 (4%) and forearm 2 (4%). Patients with sterile pre (VAC), culture and sensitivity was not turning non sterile after VAC, but 90% non-sterile turns sterile after vacuum assisted dressing. In 5 days 25% of granulation tissue formed in VAC dressing whereas only 10% in case control. Similarly, in 10 days it was 40% for VAC and 25% in case of control. Finally, in 15 days it was 70% in case of VAC and 40% in case of control. Conclusions: VAC results in better healing, with few serious complications, and a promising alternative for the management of various wounds.